21st Century Character Learning: The Role Of Media and Technology In Primary Schools During The Transition Period - Farah Nurhaliza; Zetra Hainul Putra; Neni Hermita; Deprizon (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study analyzes the role of media and technology in 21st-century character-based learning in elementary schools and its relevance in supporting children's transition from kindergarten to elementary school. Using a library research design with a qualitative approach, this study examines literature from national and international journals. The findings indicate that technology integration within the Merdeka Curriculum contributes to developing 21st-century skills (4Cs: critical thinking, creativity, communication, and collaboration) while strengthening students' character through interactive and meaningful learning. Digital platforms such as Canva prove effective in increasing student motivation and engagement, facilitating concept visualization, and fostering creativity. In the early childhood-to-elementary transition context, technology functions as an adaptive bridge supporting the shift from play-based to structured learning. Digital media enables gradual, attractive, and contextual delivery of learning materials, supporting children's school readiness including self-regulation, attention, independence, and socio-emotional adjustment. This literature review identifies three major transition barriers: cognitive overload from rapid curriculum changes, socio-emotional adjustment challenges, and limited teacher readiness in technology integration. Among various digital media strategies, gamification and visual content creation through Canva emerge as the most effective approaches, with 78% of reviewed studies reporting significant improvements in student engagement and learning motivation. The study emphasizes that successful 21st-century character-based learning depends on teachers' transformed roles as facilitators who appropriately integrate technology, apply differentiated instruction according to students' readiness, and create transition-friendly learning environments. Thus, technology use not only improves learning quality but also strengthens children's holistic readiness to enter elementary school.